Antifungal Activity of Two Root Canal Sealers against Different Strains of Candida - Jafari, Farnaz; Jafari, Sanaz; Samadi Kafil, Hossein; Momeni, Tahereh; Jamloo, Helen (Iranian Endodontic Journal, 2016)
Introduction: Microorganisms and microbial products are the main etiologic factors in pulp and periapical diseases. The present study aimed to compare the antifungal activity of two different sealers, AH-26 and MTA Fillapex against three strains of Candida, 24, 48, 72 h and 7 days after mixing. Methods and Materials: The microorganisms used in this study were Candidia albicans (ATCC 10231), Candidia glabrata (ATCC 90030) and Candidia krusei (DSM 70079). This test was based on growth of microorganisms and turbidity measurement technique using a spectrophotometer. The direct contact test was conducted by direct and indirect methods. Multiple comparisons were carried out using analysis of variances (ANOVA) with repeated measures followed by Tukey’s tests. Results: The antifungal activity of both sealers was similar in the indirect method. The antifungal activity of both sealers in the direct method was similar against Candida albicans and higher for AH-26 sealer against Candida krusei and Candida glabrata. Conclusion: The total antifungal effect of MTA Fillapex sealer was significantly less than AH-26 sealer in direct method. The antifungal effect of both sealers was similar in indirect method. Keywords: Antifungal; Antimicrobial; Candida; Endodontic Sealers